How Do Criminal Subcultures Manifest within Incarceration Institutions and Street Subcultures? A Comparative Analysis of the Subculture of Women Incarcerated in the Panevėžys Correction House and the Street Subculture of Lithuanian Skinhead Nationalists - Subačiūtė, Jurgita; Gedaminskaitė, Agnė (Kriminologijos studijos, 2018)
[full article and abstract in Lithuanian; abstract in English] This article analyzes, from a sociological and criminological perspective, two socially alienated groups: incarcerated women and the street subculture of Lithuanian skinheads, who are characterized by nationalist views and aggressive behavior. Both of these groups are socially alienated. Women serving time are naturally isolated from society. Meanwhile, participants of the skinhead subculture are stigmatized owing to their aggressive appearance: militaristic apparel and shaved heads. This stigma is caused by mass media information about these subcultures rather than by direct contact and cooperation with the participants of a criminal subculture. The aim of this investigation is to use the semistructured interview method to ascertain the manifestation of a criminal subculture in the selected study groups by evaluating the expression of the personal qualities of the participants in these subcultures, the subcultures’ traditions and policies, and the attitudes that lead to expulsion from these subcultures. The results of the investigation show that a criminal subculture can be manifested among incarcerated individuals by exoteric symbols, an asocial relationship structure, an amoral code of ethics, and traditions. It was noted that the inmates who have outside financial and material support acquire greater influence in the inmate community. The behavioural norms in the women’s incarceration institution were characteristic of not so much a criminal or closed group subculture as camaraderie in many cases: not to steal from, not to spread rumors about and not to tell on one’s fellow inmates. The qualities esteemed the most highly by the women incarcerated in the correctional institution were neutrality, impartiality, and an ability to defend one’s dignity and opinion. The use of the semistructured interview investigation method with the participants of the skinhead subcultures showed that the aggressive outbursts, which the studied subcultures manifested in defending the group’s ideas, political views, and value ideals, are understood as virility. The respondents themselves have stated that violence, vandalism, and drug addiction are the main things that lead to being expelled from the studied subcultures.